Art of ancient India : contextualizing social relations - Panikkar, Shivaji; Sheth, Abha.; Maharaja Sayajirao University of Baroda. Department of Art History and Aesthetics ([Baroda] : Maharaja Sayajirao University of Baroda : Copies available at University Publication Sales Unit, 2004)
Contributed articles presented at a conference titled theorizing India's pre-modern visual culture: issues of class, caste, gender, and sexualities at Department of Art History and Aesthetics, Maharaja Sayajirao University of Baroda, February 13th-15th, 2003.
Includes bibliographical references.
Includes words in Sanskrit
Keywords: Art, Ancient -- India; Art and society -- India